La pensión jubilar patronal en el Ecuador - Briones Murillo, Raúl (2015)
The present study was aimed at analyzing the various factors that influence the quantification of the Employer Retirement, watching to this social and economic effects generated behind this picture. Exploration reflect the social conditions are closely related to the economics of workers and their families, and what is the state's share in the resulting ratio of workers and employers……